Phenotypic screen of early-developing larvae of the blood fluke, schistosoma mansoni, using RNA interference. - M M Mourão; Nathalie Dinguirard; Glória R Franco; Timothy P Yoshino (Public Library of Science (PLoS), 2009)
RNA interference (RNAi) represents the only method currently available for manipulating gene-specific expression in Schistosoma spp., although application of this technology as a functional genomic profiling tool has yet to be explored. In the present study 32 genes, including antioxidants, transcription factors, cell signaling molecules and metabolic enzymes, were selected to determine if gene knockdown by RNAi was associated with morphologically definable phenotypic changes in early intramolluscan larval development. Transcript selection was based on their high expression in in vitro cultured S. mansoni primary sporocysts and/or their potential involvement in developmental processes. Miracidia were allowed to transform to sporocysts in the presence of synthesized double-stranded RNAs (dsRNAs) and cultivated for 7 days, during which time developing larvae were closely observed for phenotypic changes including failure/delay in transformation, loss of motility, altered growth and death. Of the phenotypes evaluated, only one was consistently detected; namely a reduction in sporocyst size based on length measurements. The size-reducing phenotype was observed in 11 of the 33 (33%) dsRNA treatment groups, and of these 11 phenotype-associated genes (superoxide dismutase, Smad1, RHO2, Smad2, Cav2A, ring box, GST26, calcineurin B, Smad4, lactate dehydrogenase and EF1alpha), only 6 demonstrated a significant and consistent knockdown of specific transcript expression. Unexpectedly one phenotype-linked gene, superoxide dismutase (SOD), was highly induced ( approximately 1600-fold) upon dsRNA exposure. Variation in dsRNA-mediated silencing effects also was evident in the group of sporocysts that lacked any definable phenotype. Out of 22 nonphenotype-expressing dsRNA treatments (myosin, PKCB, HEXBP, calcium channel, Sma2, RHO1, PKC receptor, DHHC, PepcK, calreticulin, calpain, Smeg, 14.3.3, K5, SPO1, SmZF1, fibrillarin, GST28, GPx, TPx1, TPx2 and TPx2/TPx1), 12 were assessed for the transcript levels. Of those, 6 genes exhibited consistent reductions in steady-state transcript levels, while expression level for the rest remained unchanged. Results demonstrate that the efficacy of dsRNA-treatment in producing consistent phenotypic changes and/or altered gene expression levels in S. mansoni sporocysts is highly dependent on the selected gene (or the specific dsRNA sequence used) and the timing of evaluation after treatment. Although RNAi holds great promise as a functional genomics tool for larval schistosomes, our finding of potential off-target or nonspecific effects of some dsRNA treatments and variable efficiencies in specific gene knockdown indicate a critical need for gene-specific testing and optimization as an essential part of experimental design, execution and data interpretation.